Epidemiological Characteristics and Trends of Zoonotic Diseases in China from 2015 to 2022 - Yunfei Zhang; Mengjie Geng; Yue Shi; Baijun Jin; Qian Xiong; Sheng Zhou; Jiangmei Liu; Biao Kan; Maigeng Zhou; Tian Qin; Canjun Zheng (Tropical Medicine and Infectious Disease, 2025)
This study aimed to analyze the epidemiological characteristics and incidence trends of zoonotic diseases in China from 2015 to 2022, providing evidence for zoonotic disease prevention and control strategies. Individual case data for nationally reported zoonotic diseases from the Chinese Disease Prevention and Control Information System were collected. Descriptive epidemiology and statistical methods were employed to analyze trends along with changes in their spatial, temporal, and demographic distributions. From 2015 to 2022, the annual incidence rates of leishmaniasis, Japanese encephalitis, rabies, echinococcosis, hemorrhagic fever with renal syndrome (HFRS), and schistosomiasis showed a fluctuating downward trend. The incidence rates of anthrax and leptospirosis remained relatively stable. The incidence of brucellosis declined from 2015 to 2018 but subsequently increased through 2022. Western provinces, such as Gansu, Ningxia, Qinghai, Xinjiang, and Yunnan, remain high-incidence areas for multiple zoonotic diseases, with farmers being the population at the highest risk. These findings indicate it is essential to strengthen cross-sectoral cooperation and develop region- and population-specific prevention and control strategies based on the ‘One Health’ concept, particularly in areas with high incidence rates and among high-risk populations.